Protection of CD33-modified hematopoietic stem cell progeny from CD33-directed CAR T cells in rhesus macaques - Nicholas E. Petty; Stefan Radtke; Greta Kanestrom; Emily Fields; Olivier Humbert; Salvatore Fiorenza; Mallory J. Llewellyn; George S. Laszlo; Justin Thomas; Zach Burger; Kyle Swing; Haiying Zhu; et al. (Blood Advances)
Abstract: The treatment of monogenetic disorders, such as hemoglobinopathies and lysosomal storage diseases, has markedly improved with the advent of cell and gene therapies, particularly allogeneic or gene-modified autologous stem cell transplantations. However, therapeutic efficacy is reliant on maintaining engraftment above a critical threshold. To maintain such engraftment levels, we and others have pursued approaches to shield edited cells from antibody or chimeric antigen receptor (CAR) T-cell–mediated selection. Here, we focused on CD33, which is expressed early on hematopoietic stem and progenitor cells (HSPCs) as well as on myeloid progenitors. Rhesus macaques were engrafted with HSPCs edited to ablate CD33 using either CRISPR/CRISPR-associated protein 9 or adenine base editor. Both editing strategies showed similar post-transplant recovery kinetics and yielded equivalent levels of engraftment. We then created a V-set domain–specific CAR construct (CAR33), validated its functionality in vitro, and treated both animals with autologous CAR33 T cells. CAR33 T cells expanded after infusion and caused specific depletion of CD33WT but not CD33null progeny, leading to a transient enrichment for gene-edited cells in the blood. No depletion was seen in the bone marrow stem cell compartment with CD34+CD90+ HSCs expressing lower levels of CD33 in comparison to monocytes. Thus, we show proof of concept and safety of an epitope editing–based enrichment/protection strategy in macaques.